Social behavior and welfare in Nile Tilapia - Gonçalves-De-Freitas, Eliane [UNESP]; Bolognesi, Marcela Cesar [UNESP]; Gauy, Ana Carolina Dos Santos [UNESP]; Brandão, Manuela Lombardi [UNESP]; Giaquinto, Percilia Cardoso [UNESP]; Fernandes-Castilho, Marisa [UNESP] (MDPI, 2019)
Fish social behavior can be affected by artificial environments, particularly by factors that act upon species that show aggressive behavior to set social rank hierarchy. Although aggressive interactions are part of the natural behavior in fish, if constant and intense, such interactions can cause severe body injuries, increase energy expenditure, and lead the animals to suffer from social stress. The immediate consequence of these factors is a reduced welfare in social fish species. In this paper, we consider the factors that impact on the social behavior and welfare of Nile tilapia, an African cichlid fish widely used both in fish farms and in research; this species is frequently used as a model for physiology and behavior research. This is a polygynous species whose males interact aggressively, establishing a territorial based hierarchy, where a dominant male and several subordinate males arise. When social stability is shrunk, the negative effects of prolonged fighting emerge. In this paper, we summarized how some of the common practices in aquaculture, such as classifying individuals by matching their sizes, water renewal, stock density, and environment lighting affect Nile tilapia social aggressive interactions and, in turn, impact on its welfare. We also discuss some ways to decrease the effects of aggressive interactions in Nile tilapia, such as environment color and body tactile stimulation.
Keywords: Aggressive interaction; Fighting ability; Social communication; Social rank; Social stress